2021
DOI: 10.1021/acs.molpharmaceut.1c00193
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Amikacin into Microparticles Based on Low-Molecular-Weight Poly(lactic acid) and Poly(lactic acid-co-polyethylene glycol)

Abstract: The aim of this study was to fabricate novel microparticles (MPs) for efficient and long-term delivery of amikacin (AMI). The emulsification method proposed for encapsulating AMI employed low-molecular-weight poly(lactic acid) (PLA) and poly(lactic acid- co -polyethylene glycol) (PLA–PEG), both supplemented with poly(vinyl alcohol) (PVA). The diameters of the particles obtained were determined as less than 30 μm. Based on an in-vitro release study, it was proven that the MPs (both PLA/PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The different amikacin- nanoparticles with different structures have been reported. The encapsulating of amikacin by using low-molecular-weight poly(lactic acid) (PLA) and poly(lactic acid-co-polyethylene glycol) (PLA-PEG), both supplemented with poly(vinyl alcohol) (PVA), was reported that the particle size was < 30 μm for long term release the MBC, MIC and, cytotoxicity was not determined (Glinka et al 2021 ). Another amikacin- nanoparticle is the combination of gold nanostars (GNS) and amikacin, in which it is the minimum inhibitory concentration (MIC), and minimal bactericidal concentration (MBC) were 80 and 160 µM of GNS for all strains, respectively (Aguilera-Correa et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different amikacin- nanoparticles with different structures have been reported. The encapsulating of amikacin by using low-molecular-weight poly(lactic acid) (PLA) and poly(lactic acid-co-polyethylene glycol) (PLA-PEG), both supplemented with poly(vinyl alcohol) (PVA), was reported that the particle size was < 30 μm for long term release the MBC, MIC and, cytotoxicity was not determined (Glinka et al 2021 ). Another amikacin- nanoparticle is the combination of gold nanostars (GNS) and amikacin, in which it is the minimum inhibitory concentration (MIC), and minimal bactericidal concentration (MBC) were 80 and 160 µM of GNS for all strains, respectively (Aguilera-Correa et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combining PLA with PVA also enhances the hydrophilicity and ductility of the resulting product [ 10 , 14 ]. Another finding is that PVA acts as an emulsifier when preparing materials from PLA and hydrophilic modifiers, e.g., hydrophilic drugs (W/O emulsion system) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few materials modified with AMI for wound healing have appeared in published papers; however, these concerned fabricated materials originating from natural polymers, e.g., chitosan-based porous matrices [ 31 ], alginate-based hydrogel membranes [ 32 , 33 ] and collagen [ 34 ]. In a previous work by the authors [ 15 ], a novel PLA-based material (microparticles) with encapsulated AMI was proposed. A description was given of the difficulties encountered when preparing the AMI-modified polymeric materials founded on hydrophobic synthetic polymers, in this case PLA [ 15 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their clinical use has been compromised by widespread instances of resistance [ 32 ] or adverse side effects such as ototoxicity and nephrotoxicity at high antibiotic doses [ 33 ], being the preparation of new aminoglycoside formulations that allow on-demand drug delivery a plausible solution to this sticky issue. Poly (lactic acid) or poly (lactic-co-glycolic acid)-based systems have been commonly employed for AGA encapsulation [ 34 , 35 , 36 ]; however, the formation of PLGA and PLA particles requires the use of organic solvents. This is a major drawback since, among other effects, the use of organic solvents can produce relevant toxicological effects and, moreover, can reduce the scalability and practical industrial application of these systems.…”
Section: Introductionmentioning
confidence: 99%